Four days high fat diet modulates vitamin D metabolite levels and enzymes in mice. Issue 1 (January 2021) - Bonnet, Lauriane; Karkeni, Esma; Couturier, Charlène; Astier, Julien; Defoort, Catherine; Svilar, Ljubica; Tourniaire, Franck; Mounien, Lourdes; Landrier, Jean-François
Abstract : Obesity is classically associated with low serum total and free 25(OH)D. Hypotheses have been advanced to explain this observation but mechanisms remain poorly understood, and notably priming events that could explain such association. We investigated the impact of short-term high fat (HF) diet to investigate early events occurring in vitamin D metabolism. Male C57BL/6J mice were fed with a control diet (control group) and HF diet for 4 days. HF fed mice displayed similar body weight to control mice but significantly increased adiposity, together with a decrease of free 25(OH)D concentrations, which could be explained at least in part by a decrease of Cyp2r1 and Cyp3a11 expression in the liver. An increase of 1, 25(OH)2 D concentration was also observed and could be explained by a decrease of Cyp24a1 expression observed in the kidney. In white adipose tissue (WAT), no modification of vitamin D metabolites quantity detected by liquid chromatography-tandem mass spectrometry (LC-MS/MS). Nevertheless, an increase of Cyp2r1 and Cyp27a1 mRNA expression and a decrease of Cyp27b1 mRNA expression could suggest a possible storage of 25(OH)D in WAT at long-term. Our data are supportive of an active role of HF diet in mediating a priming effect leading the well-established perturbation of the vitamin D metabolism associated with obesity, including a decrease of free 25(OH)D and modulation of expression of genes involved in vitamin D metabolism.